2015
DOI: 10.1631/jzus.a1400172
|View full text |Cite
|
Sign up to set email alerts
|

Research on the slagging characteristics of blended coals in a pilot-scale furnace

Abstract: This paper applies digital image techniques to observe the slagging characteristics of blended coals in a pilot-scale furnace. Collected deposit samples were analyzed by scanning electron microscopy linked with energy-dispersive X-ray analysis (SEM-EDX), X-ray diffraction (XRD), and X-ray Fluorescence (XRF) to acquire the microstructure, chemical composition, and mineralogy. The deposit thickness of three blends was analyzed between their parent coal A (Datong) and coal B (Shan), and we noted that the time to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…This also proves that AsA biosynthesis is not the only factor affecting the AsA maintenance level of the fruit of A. eriantha . In addition, in this study, the activity of DHAR2 during the fruit growth period was much higher than that of MDHAR5, which was consistent with the previous results [ 25 ]. We speculated that DHAR2 played a more important role in the regeneration cycle pathway of AsA.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This also proves that AsA biosynthesis is not the only factor affecting the AsA maintenance level of the fruit of A. eriantha . In addition, in this study, the activity of DHAR2 during the fruit growth period was much higher than that of MDHAR5, which was consistent with the previous results [ 25 ]. We speculated that DHAR2 played a more important role in the regeneration cycle pathway of AsA.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have shown that the increase of ascorbic acid content can be achieved by increasing the expression of GalLDH , such as in apple [ 13 ], rice [ 23 ] and potato [ 24 ]. Studies on kiwifruit showed that GalLDH activity in mature fuit of different genotypes was significantly correlated with T-AsA and AsA [ 25 ]. Genes (high expression) and key enzymes (high activity) in the L-galactose pathway that are obviously related to AsA content may be important factors for maintaining high AsA content in fruit, but they are not necessarily the only factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study employed a convenient and snowball sampling because of the limited number of available and accessible candidates (Hendricks & Blanken, 1992; Zhou, 2017). Participants were recruited online from Hunan and Hubei Province.…”
Section: Methodsmentioning
confidence: 99%
“…There is a need to identify the types of coal blends in coal-fired power plants that will enhance boiler safety, improve combustion efficiency and reduce pollutant emissions. Considerable research has been conducted on the combustion behavior of coal blends, including the ignition process, NOx emissions, burnout behavior and slagging behavior, using thermogravimetric analysis and drop-tube furnaces (Cloke et al, 2002;Biswas et al, 2006;Chi et al, 2010;Moon et al, 2013;Sarkar et al, 2013;Zhou et al, 2015). In a coal-fired power plant, usually multiple coal types are burned, and the blended composition is unknown and even unpredictable after delivery and accumulation in stocks.…”
Section: Introductionmentioning
confidence: 99%